MAQASID SYARI’AH SA’ID AL-ASYMAWI - Mohamad Thoyyib Madani, MA; Rifki Rufaida, M.H. (IQTISODINA, 2019)
Benefit as the core of maqâshid al-syarî‘ah, has an important role in determining Islamic law. Because Islamic law was revealed to have the goal to realize the benefit of the people both in the world and the hereafter. Thus actually maqashid al-syarî‘ah has a very close relationship with the istinbath method of law, in other words that each istinbath method of law is based on benefit. The methods used by the ulama in exploring the benefit are of two kinds namely: First the ta'liîlî method (substantive analysis method) which includes qiyas and istihsân. The two istishlâhî methods (the method of benefit analysis) which include al-mashahah al-mursalah and al-dharî'ah both the categories of sadd al-dzarî'ah and fath al-dzarî'ah.